Formin homology 2 domains occur in multiple contexts in angiosperms - Cvrcková, Fatima; Novotný, Marian; Pícková, Denisa; Zárský, Viktor (BMC genomics, 2004)
BACKGROUND: Involvement of conservative molecular modules and cellular mechanisms in the widely diversified processes of eukaryotic cell morphogenesis leads to the intriguing question: how do similar proteins contribute to dissimilar morphogenetic outputs. Formins (FH2 proteins) play a central part in the control of actin organization and dynamics, providing a good example of evolutionarily versatile use of a conserved protein domain in the context of a variety of lineage-specific structural and signalling interactions. RESULTS: In order to identify possible plant-specific sequence features within the FH2 protein family, we performed a detailed analysis of angiosperm formin-related sequences available in public databases, with particular focus on the complete Arabidopsis genome and the nearly finished rice genome sequence. This has led to revision of the current annotation of half of the 22 Arabidopsis formin-related genes. Comparative analysis of the two plant genomes revealed a good conservation of the previously described two subfamilies of plant formins (Class I and Class II), as well as several subfamilies within them that appear to predate the separation of monocot and dicot plants. Moreover, a number of plant Class II formins share an additional conserved domain, related to the protein phosphatase/tensin/auxilin fold. However, considerable inter-species variability sets limits to generalization of any functional conclusions reached on a single species such as Arabidopsis. CONCLUSIONS: The plant-specific domain context of the conserved FH2 domain, as well as plant-specific features of the domain itself, may reflect distinct functional requirements in plant cells. The variability of formin structures found in plants far exceeds that known from both fungi and metazoans, suggesting a possible contribution of FH2 proteins in the evolution of the plant type of multicellularity.
Keywords: sekundární struktura proteinů; Conserved Sequence; Protein Structure, Secondary; rostlinné geny; Sequence Homology, Amino Acid; aktiny; fylogeneze; Arabidopsis; Genes, Plant; cytoskeletální proteiny; Molecular Sequence Data; terciární struktura proteinů; Magnoliopsida; sekvence aminokyselin; Protein Structure, Tertiary; molekulární modely; sekvenční homologie aminokyselin; Actins; Phylogeny; Cytoskeletal Proteins; Amino Acid Sequence; konzervovaná sekvence; Models, Molecular; molekulární sekvence - údaje